Efektivitas Model Workshop Berorientasi P-21 pada Motivasi Guru Sekolah Dasar - Maryani, Ika; Tutur Martaningsih, Sri; Fatmawati, Laila (Jurnal MIPA dan Pembelajarannya, 2023)
21st century learning has great challenges for primary school teachers. Teachers must have professional competence to develop 21st century skills-oriented learning. This study aims to produce a training model for elementary school teachers in 21st century learning. This study uses Research and Development with ADDIE (Analysis, Design, Develop, Implement, and Evaluate) procedures. The trial design used a one group pretest-posttest experimental design. The effectiveness of the model is measured on the understanding and motivation of teachers during the workshop. The subjects of this study were Muhammadiyah elementary school teachers located in Minggir District, Sleman Regency, DIY. The data analysis technique used descriptive statistics (mean, standard deviation, and categorization). The results of the content validity test based on the input of 2 experts who were analyzed using Aiken V showed that in the aspects of content, presentation, and language each got a value of 0.931; 0.918; and 0.934 which means valid. Motivation of 17% of participants is in the high category, 74% is in the medium category, and 9% is in the low category. Self-efficacy, intrinsic values, cognitive strategies, and self-regulation of participants were in the good category. The four supporting factors still need to be improved. While anxiety is in the moderate category, anxiety must be minimized so that the training can be more effective.